The Synthesis of Triamine Group Modified Silica Hybrid Material Coated on Muara Kencan Iron Sand for Hg (II) Adsorption - Ricka Prasdiantika; Dony Allan Pratama; Agustien Zulaidah; Eny Apriyanti; Suharman Suharman (Department of Chemistry Faculty of Science and Technology Walisongo, 2022)
Hg metal was toxic and harmful to the environment because it does not biodegradation, can accumulate in living things, and pollute waters. One method that can be used was adsorption by inorganic-organic hybrid materials. This study aims to synthesize a triamine group modified silica hybrid material coated on iron sand or Magnetic Materials@Silica@Triamine (MM@SiO2@TA) to adsorb Hg(II) metal ions. The study began with the preparation of the iron sand of Muara Kencan Beach using magnets, washing using a solution of 1 M HCl and 0.5 M HF, and coating the material using sodium silica (SiO 25.5-28.5%) modified by a 99% triamine group with co-precipitation. The XRF characterization results showed that the magnetic material of the iron sand of Muara Kencan Beach has an iron oxide (magnetite) content of 73.31%. The iron oxide content increased after washing with HCl solution to 79.12% and HF solution to 81.81%. The results of FTIR, XRD, and TEM characterization showed that the MM@SiO2@TA was successfully synthesized with a size of 63.43 nm. The MM@SiO2@TA was tested to adsorb metal ion Hg(II) at a concentration of 100 ppm, pH 6, and a contact time of 1 hour. The AAS results showed that MM@SiO2@TA could adsorb metal ions Hg(II) as much as 60.82 ppm or 60.82%.